THE IMPACT OF WORDWALL MEDIA ON STUDENTS' LEARNING ACHIEVEMENT AT STATE ELEMENTARY SCHOOL 0513 AEK LANCAT - Ongku Mahmul Daulay; Nurhalimah Harahap (Darul Ilmi Bina Insan Foundation, 2024)
This research aims to evaluate the impact of using the Wordwall website for online quizzes on student learning outcomes in science subjects. The study employs a quantitative research method with a pre-experimental design, specifically a one-group pretest-posttest type. The population consists of all fourth-grade students at SD Negeri 0513 Aek Lancat, with a saturated sampling technique yielding a sample size of 20 students. Data collection was conducted using post-test multiple-choice questions. Hypothesis testing results indicate that Wordwall media significantly influences student learning outcomes, with t = 5.546 at α = 0.05 and degrees of freedom df (n-1) = 21, where the t-table value is 2.076. Thus, it can be concluded that Wordwall-based quiz media positively affects the science learning outcomes of fourth-grade students at SD Negeri 0513 Aek Lancat.